Pentingnya Self Compassion untuk Setiap Individu - Handryani, Monica; Dewi, Ira Kesuma (Universitas Medan Area, 2025)
Self-compassion is affection directed within oneself, concerning oneself we are the object of attention and concern when faced with suffering. Self-compassion is important for every individual because when someone experiences life experiences bad, the individual will still treat himself warmly and well so that they experience more positive emotions than negative emotions. Also added that Self-compassion also provides psychological strength such as happiness, optimism, positive affect, self-efficacy, and psychological well-being. This research aims to find out the importance of self-compassion in each individual and how Self Compassion plays a role important in every problem that every individual faces in everyday life. This research uses the literature study method. This research was conducted by reviewing ten journals that relate to self-compassion with different research subjects. Results research shows applying self-compassion allows a person to engage in activities that arouse a person's sense of happiness and well-being. Study proves that there is a relationship between self-compassion and healthy living habits. Healthy living habits such as a healthy diet, adequate exercise and sleep, and stress management were found to have a relationship with self-compassion.